2021
DOI: 10.3389/fonc.2021.679244
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR: A Potential Prognostic Factor and Therapeutic Target in Human Cancers

Abstract: Long non-coding RNAs (lncRNAs) are emerging as crucial regulators of gene expression and physiological processes. LncRNAs are a class of ncRNAs of 200 nucleotides in length. HOX transcript antisense RNA (HOTAIR), a trans-acting lncRNA with regulatory function on transcription, can repress gene expression by recruiting chromatin modifiers. HOTAIR is an oncogenic lncRNA, and numerous studies have determined that HOTAIR is highly upregulated in a wide variety of human cancers. In this review, we briefly summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 136 publications
0
21
0
1
Order By: Relevance
“…HOTAIR mediates epigenetic changes that repress genes by shuttling PRC2 and LSD1 to their targets (70). In multiple cancers HOTAIR promotes tumor growth, metastasis, migration and epithelial mesenchymal transition (70)(71)(72). HOTAIR is increased by estrogen in breast cancer cells (73), is associated with poor prognosis in endometrial cancer (74) and mediates endometrial cancer cell proliferation and invasion (75).…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR mediates epigenetic changes that repress genes by shuttling PRC2 and LSD1 to their targets (70). In multiple cancers HOTAIR promotes tumor growth, metastasis, migration and epithelial mesenchymal transition (70)(71)(72). HOTAIR is increased by estrogen in breast cancer cells (73), is associated with poor prognosis in endometrial cancer (74) and mediates endometrial cancer cell proliferation and invasion (75).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that GAS5 could inhibit cell migration and invasion and promote autophagy by targeting miR-222-3p through the GAS5/PTEN-signaling pathway in colorectal cancer (53), and this targeting relationship was also predicted in the Exo-LT ceRNA network. HOTAIR is a well-known oncogenic lncRNA, and studies have determined that HOTAIR is highly up-regulated in various human cancers, such as breast cancer, lung cancer, gastric cancer, and liver cancer (54). Erdos et al found that HOTAIR binds and positively or negatively modulates the expression of genes involved in adipose tissue-speci c pathways, including adipogenesis (55).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA HOTAIR interacts with PRC2 and induces H3K27me3-mediated repressive methylation on the promoter of tumor suppressive genes such as PTEN (phosphatase and tensin homolog) and JAM2 (junctional adhesion molecule B). It can also interact with LSD1 to induce H3K4-demethylation to activate the gene expression on the promoter of LDHA (lactate dehydrogenase A) and CCNA1 (cyclin A) genes, thereby promoting EMT and metastasis [ 133 ]. LncRNA MALAT1 sequesters miR-126-5p and enhances the expression of Slug and Twist to facilitate EMT and metastasis in colorectal cancers [ 141 ].…”
Section: Lncrnas In Human Diseasesmentioning
confidence: 99%
“…LncRNA HOTAIR recruits PRC2 to the promoter of gene encoding miR-7 to induce repressive H3K27me3 methylation. Further, the upregulation of its downstream targets such as c-Myc and Twist through miR-7/SETDB1 (SET domain bifurcated histone lysine methyl transferase 1)/STAT3 axis enhances the stemness in breast cancers [ 133 , 134 ]. The tumor suppressor lncRNA LBCS is downregulated in bladder cancers, which otherwise recruits hnRNPK and EZH2 to the promoter of SOX2 gene to induce H3K27me3 repressive tri-methylation, thus suppressing SOX2 expression [ 156 ].…”
Section: Lncrnas In Human Diseasesmentioning
confidence: 99%